Jatrophone: a cytotoxic macrocylic diterpene targeting PI3K/AKT/NF-κB pathway, inducing apoptosis and autophagy in resistant breast cancer cells - Khawlah Shari; Rania A. El Gedaily; Rasha M. Allam; Khaled M. Meselhy; Amal E. Khaleel; Essam Abdel-Sattar (BMC, 2023)
Abstract Background Breast cancer is a prevalent malignant tumor that affects women worldwide. The primary challenge in treating breast cancer is combating drug resistance, which contributes to relapse and metastasis. Jatrophone is a unique macrocyclic jatrophane diterpene found in various Jatropha and Euphorbia species. It possesses diverse biological and pharmacological activities, including anticancer activity. However, it is unclear whether jatrophone can overcome drug resistance in breast cancer. Methods This study includes the investigation of the cytotoxicity of jatrophone on doxorubicin-resistant breast cancer cells (MCF-7ADR) and the underlying molecular mechanisms. The effects of jatrophone on cell viability were determined using the sulforhodamine B (SRB) assay, while flow cytometry was used to evaluate cell cycle progression, apoptosis, and autophagy. A scratch assay was conducted to observe cell migration, and western blotting was used to measure downstream protein levels (PI3K, AKT, and NF-κB). Unpaired Student's t-tests were used for comparison between the two groups and the results were analyzed by one-way ANOVA with Tukey- Kremer post hoc test. Results It was shown that jatrophone exhibited potent cytotoxic activity on MCF-7ADR cells in a dose-dependent manner, with an IC50 value of 1.8 µM. It also significantly induced cell cycle S and G/M phase arrest. Interestingly, jatrophone induced both early and late apoptotic cell death, as well as autophagic cell death, with negligible necrosis. Furthermore, jatrophone treatment diminished the migration of MCF-7ADR cells. At the molecular level, jatrophone treatment significantly down-regulated the expression levels of PI3K, AKT, and NF-κB. β. Conclusions The results of the study suggest that jatrophone decreases the proliferation of MCF-7/ADR cells at a low micromolar concentration; induces cell cycle arrest; promotes apoptotic, and autophagic cell death; inhibits migration and EMT; and works on resistance by a mechanism involving the inhibition of the PI3K/Akt/ NF-κB pathway. These findings provide evidence of the potential of jatrophone to be a promising lead compound for targeting doxorubicin-resistant breast cancer cells and could be further investigated for its clinical application as a chemotherapy adjuvant.